Commenting on Code, Considering Data's Bottleneck. - Torres, Edwin; Saba, Walid (Communications of the ACM, 2018)
The article discusses the role of comments in software code. Topics include the formatting of computer software programming, the lack of clarity involved in some programming languages, and the significance of data distribution in relation to data science. The importance of data preparation in relation to knowledge acquisition is addressed.